Inclusive physical education in secondary schools: a bibliometric analysis of publications from 2000 to 2024 - Iman Rubiana; Sugeng Purwanto; Muhammad Hamid Anwar (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction Inclusive physical education has gained attention globally due to its importance in fostering equity and participation for all students. However, research on this topic, particularly in secondary schools, remains limited.